2014
DOI: 10.5194/nhess-14-1155-2014
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami hazard assessment in the southern Colombian Pacific basin and a proposal to regenerate a previous barrier island as protection

Abstract: Abstract. In this study, the tsunami hazard posed to 120 000 inhabitants of Tumaco (Colombia) is assessed, and an evaluation and analysis of regenerating the previous El Guano Island for tsunami protection is conducted. El Guano Island was a sandy barrier island in front of the city of Tumaco until its disappearance during the tsunami of 1979; the island is believed to have played a protective role, substantially reducing the scale of the disaster. The analysis is conducted by identifying seismotectonic parame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
1
4
1
8
Order By: Relevance
“…On Cascajal Island, there is much less variability in terms of inundation extent and inundation depth: 12.6% of the island is flooded between 0.3 m and 0.01 m. Restrepo and Otero (2007) found that the maximum tsunami wave height for Cascajal Island in Buenaventura ranged from 2.6 to 4 m depending on the generation scenario evaluated, in contrast to the maximum heights obtained for the same area in this study which did not exceed 0.7 m. In the case of Tumaco, these differences are not as marked with respect to what was found by Quiceno and Ortiz (2001), Cardona et al (2005), Sánchez and Puentes (2012) and Otero, Restrepo, and Gonzalez (2014). Beyond the seismic scenario used in each study, this heterogeneity in results concerning Buenaventura Bay could plausibly be explained by considering the role of the marine and coastal morphology, both in the exterior and interior zone of the bay.…”
Section: Inundation Depthcontrasting
confidence: 60%
See 4 more Smart Citations
“…On Cascajal Island, there is much less variability in terms of inundation extent and inundation depth: 12.6% of the island is flooded between 0.3 m and 0.01 m. Restrepo and Otero (2007) found that the maximum tsunami wave height for Cascajal Island in Buenaventura ranged from 2.6 to 4 m depending on the generation scenario evaluated, in contrast to the maximum heights obtained for the same area in this study which did not exceed 0.7 m. In the case of Tumaco, these differences are not as marked with respect to what was found by Quiceno and Ortiz (2001), Cardona et al (2005), Sánchez and Puentes (2012) and Otero, Restrepo, and Gonzalez (2014). Beyond the seismic scenario used in each study, this heterogeneity in results concerning Buenaventura Bay could plausibly be explained by considering the role of the marine and coastal morphology, both in the exterior and interior zone of the bay.…”
Section: Inundation Depthcontrasting
confidence: 60%
“…The present study calculated maximum height and inundation depth to evaluate the tsunami hazard through a deterministic approach in the areas of Tumaco and Buenaventura, specifically the islands of Tumaco, Morro, and Cascajal. Previous studies have evaluated the tsunami hazard in the same areas (Quiceno and Ortiz 2001;Cardona et al 2005;Restrepo and Otero 2007;Sánchez and Puentes 2012;Otero, Restrepo, and Gonzalez 2014); however all defined the tsunami generation source via a homogeneous slip which does not best represent the initial condition of tsunami waves in nearby fields (Ulutas 2013). We argue that our approach which considered non-homogeneous slip distribution better represents initial condition of tsunami.…”
Section: Inundation Depthmentioning
confidence: 90%
See 3 more Smart Citations